AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN WESTLIFE SELECTED SONG LYRICS - Melania Fitriani; Endang Susilawati Endang; Eni Rosnija (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research aims to identify the types of figurative language most often used in Westlife-selected songs. The Research Design used in this research is Qualitative Research with content analysis of lyric scripts. This study analyzed the data by selecting eight Westlife songs, reading song lyrics, identifying figurative language, and then Analyzing the figurative language used in poetry. Perrine's (1983) theory is familiar to analyzing data related to types of figurative language. This research reveals that there is figurative language in each song lyric chosen and the figurative language used varies. The research results show that there are seven types of figurative language used in Westlife's Selected Song: metaphor, personification, hyperbole, simile, repetition, Symbol, and Metonymy the results show that the figurative language most often found in Westlife's Selected Song is Metaphor 40%. The conclusions of this study are figurative language is used to compare or explain something so that sentences become more alive, make sentences more meaningful and memorable, increase the attractiveness of literary works, and bring the writer and readers closer. Keywords: Figurative language, song analysis, Westlife